Phonological stylistics in the potery of Masar Ryad: parallism model - Gawad Dagher, Hijra; Dawod Salman , Prof.Dr.Laith (Basra studies journal, 2022)
The poet, Massar Riyad, is an Iraqi poet, a contemporary poet who is born with the Iraqis and grows with their pain and becomes a friend of their childhood and youth. He has his own style of writing, and he was significant of sadness because of the environment in which he grew up and chose to express its details through his poems. The issue of the homeland, whether by reviewing the tragedies that it passed or passed through, or documenting some crimes against humanity that took place in Mesopotamia, and one of the most prominent stylistic phenomena in his poetry is the parallel phenomenon that researchers include within the internal rhythm of poetry. This research deals with this phenomenon of parallelism at the levels: phoneme, morphological, and compositional, with examples from the poet's poems accompanied by analysis.